Slow down for manatees - Arnosky, Jim. (New York : G.P. Putnam's Sons, 2010)
Injured by a passing motorboat, a pregnant manatee is rescued and taken to an aquarium to recover and have her baby in a safe environment.
Keywords: Manatees -- Fiction; Wildlife conservation -- Fiction